Studi Kausal Mengenai Hubungan Self Esteem dan Kualitas Hidup pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Ahmad Mumtaz Tauba; Andri Nurmansyah; Yolanda Anastasia Sihombing (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Individuals who experience GGK and have undergone hemodialysis will experience many changes in their lives. This can affect the patient's psychological condition. Changes that occur can have an impact on individual perceptions related to their lives including the quality of their lives and perceptions about themselves including self esteem. To find out the relationship of self esteem with the quality of life in chronic kidney failure patients who are undergoing hemodialysis in the hemodialysis room of RSUD R Syamsudin SH Sukabumi City in 2025. Research uses correlational design. The number of samples was 219 people. The instruments used were the CSEI and KDQOL-S questionnaire. The statistical test used is Chi Square's correlation. There is a relationship between self esteem and the quality of life of chronic kidney failure patients who are undergoing hemodialysis, the results of the chi square test with a p-value of 0.00 or smaller than the alpha value (a = 0.05). The results of this study can provide information for RSUD R Syamsudin SH to increase health knowledge and insight to improve the quality of life of chronic kidney failure patients in hemodialysis. One step that can be taken is to provide education to increase the patient's self esteem.